National guideline for the management of suspected sexually transmitted infections in children and young people. Issue 4 (1st April 2003) - Thomas, A; Forster, G; Robinson, A; Rogstad, K
Abstract : The Children Act 1989 1 defines a child as "a person who has not yet reached 18 years of age." In England, Wales, and Scotland the present age of consent for heterosexual and homosexual sex is 16 years and in Northern Ireland it is 17 years. The proportion of young people who report heterosexual intercourse before the age of 16 years increased in the 1990s compared with the previous decade. 2